Diet, metabolic mediators, and cancer risk - Watling, CZ (2022)
Colorectal, breast, and prostate cancer account for nearly a third of all diagnosed cancers, and some dietary factors may influence risk. Moreover, circulating insulin-like growth factor-I (IGF-I) concentrations have been positively associated with risks of colorectal, breast, and prostate cancer, and IGF-I might mediate some diet-cancer associations. This thesis investigates the associations of dietary factors, IGF-I concentrations, and IGF-I related cancers among participants in the UK Biobank cohort.